2005
DOI: 10.1590/s0080-62342005000100003
|View full text |Cite
|
Sign up to set email alerts
|

A auto-estima de indivíduos que foram submetidos à cirurgia de revascularização do miocárdio

Abstract: This is descriptive and correlational study that measured the self-esteem of individuals submitted to coronary artery bypass graft surgery and correlated the self-esteem with socio-demographic and clinical variables. A sample of 97 outpatients was interviewed. Data were analyzed by means of descriptive statistics, Pearson's Correlation test, Mann-Whitney and Kruskal Wallis tests. The reliability of the scale was verified (Cronbach alfa was 0.79) and the average for self-esteem was found to be 32.22 (possible r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 13 publications
0
16
0
9
Order By: Relevance
“…On a previous study, with a similar population performed at the same teaching hospital, the authors found that women presented with worse self-esteem, probably related to advanced age and low education level (1) . Also, the cultural tendency pointed these older age women to domestic roles, as a good mother and wife, which may have influenced the self-evaluation of the group regarding selfesteem.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…On a previous study, with a similar population performed at the same teaching hospital, the authors found that women presented with worse self-esteem, probably related to advanced age and low education level (1) . Also, the cultural tendency pointed these older age women to domestic roles, as a good mother and wife, which may have influenced the self-evaluation of the group regarding selfesteem.…”
Section: Discussionmentioning
confidence: 87%
“…Elevated self-esteem of patients was demonstrated in this study (Table 3). Low self-esteem patients would, most likely, have lower expectation towards their performance for promoting and keeping to the necessary changes for recovery (1) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations